Problematika Penghapusan Batasan Jumlah Anggota Wantimpres Melalui Teori Pilihan Rasional: Problems of Eliminating Limits on the Number of Wantimpres Members Through Rational Choice Theory - Irma Idris; Gusnaeni Bachtiar; Wiranti Wiranti (Constitution Journal, 2025)
This study uses a normative research method with a conceptual approach to connect the principle of effectiveness with the Rational Choice theory on the impact of eliminating the limit on the number of members of the Presidential Advisory Council (Wantimpres). The purpose of this study is to analyze Law Number 64 of 2024 concerning Amendments to Law Number 19 of 2006 concerning the Presidential Advisory Council (Wantimpres) which has been agreed upon in a Plenary Meeting held on Thursday, September 19, 2024 in the Plenary Meeting Room, Nusantara II Building, DPR RI, Senayan, Jakarta with its implications for the effectiveness of Wantimpres' performance which has not been proven significant. Although the changes in the legislation are intended to strengthen Wantimpres. However, on the other hand, without any member limits and competency requirements, it is difficult to guarantee that Wantimpres' performance will function more as an effective supporting organ for the president. Although flexibility in the number of members is expected to increase effectiveness, further evaluation is needed to ensure that the changes truly strengthen Wantimpres' role and function in supporting a more optimal government system. By giving full authority to the president to determine the number of members, it raises questions regarding Wantimpres' effectiveness and relevance. Given the importance of institutional analysis, it is necessary to ensure that these changes support Wantimpres' function as an effective advisor to the president. Abstrak Penelitian ini menggunakan metode penelitian normatif dengan pendekatan konseptual untuk menghubungkan prinsip efektivitas dengan teori Pilihan Rasional atas dampak dari penghapusan batasan jumlah anggota Dewan Pertimbangan Presiden (Wantimpres). Tujuan penelitian ini adalah untuk menganalisis Undang-Undang Nomor 64 Tahun 2024 tentang Perubahan atas Undang- Undang Nomor 19 Tahun 2006 terkait Dewan Pertimbangan Presiden (Wantimpres) yang telah disepakati dalam. Rapat paripurna yang digelar pada Kamis, 19 September 2024 di Ruang Rapat Paripurna, Gedung Nusantara II, DPR RI, Senayan, Jakarta dengan implikasinya terhadap efektivitas kinerja Wantimpres yang belum terbukti signifikan. Meskipun perubahan dalam peraturan perundang-undangan ini bertujuan untuk memperkuat Wantimpres. Namun di sisi lain, tanpa adanya batasan anggota dan syarat kompetensi, sulit menjamin bahwa kinerja Wantimpres akan lebih berfungsi sebagai organ pendukung yang efektif bagi presiden. Meskipun fleksibilitas terhadap jumlah anggota diharapkan mampu meningkatkan efektivitas, namun perlu melakukan evaluasi lebih lanjut untuk memastikan bahwa perubahan tersebut benar-benar memperkuat peran dan fungsi Wantimpres dalam mendukung sistem pemerintahan yang lebih optimal. Dengan memberikan kewenangan penuh kepada presiden untuk menentukan jumlah anggota, memicu pertanyaan terkait efektivitas dan relevansi Wantimpres. Mengingat pentingnya analisis kelembagaan, perlu dipastikan bahwa perubahan ini mendukung fungsi Wantimpres sebagai pemberi nasihat yang efektif bagi presiden.